Civil Law Provisions on the Application of Compensation for Victims of Unlawful Arrest Based on Progressive Legal Theory - Hardiansyah Putra; Siti Rodiah; Utari Dewi Fatimah (UNISSULA, 2025)
Compensation for victims of wrongful arrest in Indonesia is regulated under Article 9 of Government Regulation Number 92 of 2015, which determines minimum and maximum compensation amounts based on the severity of harm suffered by victims. This study aims to analyze the implementation of compensation provisions for wrongful arrest victims, examine the relevance of civil law principles in addressing the resulting material and immaterial losses, and formulate an ideal compensation framework based on progressive legal theory. Using a descriptive-analytical method with a juridical-normative approach, the research relies on secondary data consisting of primary, secondary, and tertiary legal materials, supported by the analysis of relevant court decisions and doctrinal literature. The findings reveal a significant gap between normative regulations and judicial practice, where compensation is largely limited to material aspects and neglects immaterial harms such as psychological trauma, social stigma, and loss of reputation. Consequently, the study concludes that Article 9 of Government Regulation Number 92 of 2015 requires reformulation through a progressive, human-centered approach that integrates civil liability principles and social security mechanisms to ensure comprehensive, proportional, and substantive restitution for victims of wrongful arrest.